1996
DOI: 10.1088/0022-3727/29/6/017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of demixing effect on the temperature in wall-stabilized arcs

Abstract: The demixing effect in a wall-stabilized arc leads to sulphur depletion in the central part of the arc where the ratio between fluorine concentration and sulphur concentration becomes higher than six. We have calculated material functions for different real or fictitious gases , with (specific heat, electrical and thermal conductivities, net emission coefficient) and used them in a one-dimensional model based on Patankar's algorithms. The electric field and the temperature radial profile have been calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Although the physical phenomena in a d.c. plasma torch are not completely known, some authors [1][2][3][4][5][6] have proposed models of this system in a good agreement with experimental results. At the same time, numerous experimental and theoretical works have been published on the study of the particle momentum and heat transfer to the particles [7][8][9][10][11], and to gain a better knowledge of the correlation between the properties of the spray and the operating conditions [12].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although the physical phenomena in a d.c. plasma torch are not completely known, some authors [1][2][3][4][5][6] have proposed models of this system in a good agreement with experimental results. At the same time, numerous experimental and theoretical works have been published on the study of the particle momentum and heat transfer to the particles [7][8][9][10][11], and to gain a better knowledge of the correlation between the properties of the spray and the operating conditions [12].…”
Section: Introductionmentioning
confidence: 67%
“…The model of the d.c. plasma torch, described in previous works [5,6], is based on the following hypothesis: the governing equations are written in an axisymmetric system of coordinates, the operation of the torch is assumed to be in steady state and the flow is laminar. We supposed the plasma to be in local thermodynamic equilibrium (LTE) and the radiation effects are considered through the net emission coefficient at atmospheric pressure.…”
Section: Assumptions and Governing Equations Of The Plasmamentioning
confidence: 99%
“…This system transition occurs between the electronically excited state A 2 + at 5.4 eV and the fundamental state X 2 r of NO. The ground state X 2 r is spin splitted into two components, X 2 1/2 , X 2 3/2 , and belongs to a transition case which goes from coupling case 'a' to case 'b'. The electronic state 2 belongs strictly to case 'b'.…”
Section: 26mentioning
confidence: 99%
“…Radiation is often an important phenomenon of energy transport in thermal plasmas and the calculation of the divergence of the radiative flux is needed in arc or plasma torch modelling. It has been demonstrated that the use in the energy equation of a net emission coefficient (NEC) defined by Lowke [1] as the divergence of the radiative flux at the centre of an isothermal sphere, allows to compute with a satisfactory accuracy, the temperature of the hottest regions of the plasma [2]. As the maximum temperature is often higher than 10 000 K, the radiation of the hottest regions is mainly due to atomic species (neutrals and ions); in these conditions the NEC was calculated taking only into account the atomic species, even for plasmas created in molecular gases [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…So the modelling of the attachment of the arc to the cathode and the entire domain of the stabilized discs are not taken into account. We use literature results [25][26][27] based on experimental and theoretical results, considering that this kind of configuration can be represented with the modified Elenbass-Heller equation taking into account the radiation. So this equation will be resolved in the AE section.…”
Section: Other Assumptionsmentioning
confidence: 99%